A novel approach to improve the nutritional value of black gram (Vigna mungo L.) by the combined effect of pre-gelatinization and fermentation by Lactobacillus sp. E14 and Saccharomyces cerevisiae MK-157: Impact on morphological, thermal, and chemical structural properties. (30th December 2022) - Ali, Syed Arsalan; Saeed, Syed Muhammad Ghufran; Ejaz, Uroosa; Baloch, Muneera Naz; Sohail, Muhammad
Abstract: An economical technique to obtain functional black gram flour was investigated, with reduced anti-nutritional factors, increased antioxidants, and improved technological properties. Black gram seeds were pre-gelatinized, and solid state fermentation conditions (inoculum size, incubation temperature, and incubation time) were optimized by central composite design. The strains of Lactobacillus sp. E14 and Saccharomyces cerevisiae MK-157 were selected on their ability to produce phytase enzyme and radical scavenging activity. The values of phytase and antioxidant activities predicted by the model correlated with the experimental values which showed the accuracy of the model. The fermentation of raw and gelatinized flour by S. cerevisiae MK-157 resulted in improved antioxidant (88.41%) and phytase activity (17.52 IU/mL), respectively in comparison to Lactobacillus sp. E14. Morphological and chemical structural analysis depicted the disruption of the substrate, depolymerization of starch and protein content, and presence of polyphenolic compounds. The elucidation of the flour through differential scanning calorimetry revealed the formation of hydrogen bonds in leached starch chains due to fermentation which altered the thermal behavior of starch. Therefore, this study provides an ideal approach to ferment raw and gelatinized black gram flour. Highlights: Sustainable and economical method of fermentation of black gram was developed. Optimization of fermentation parameters by central composite design. S. cerevisiae MK-157 increased antioxidant-88.41% and phytase activity-17.52 IU/mL. FTIR revealed the presence of polyphenols and depolymerization of macromolecules. Differential scanning calorimetry was used to investigate the thermal properties.